Drum song and spirit mask : a multiple-eyed seeing Indigenous methodological framework for ethical documentary filmmaking ; Drum song : the rhythm of life : documentary trailer, treatment one sheet, and slide deck : a thesis and exegesis submitted to Te Kuenga Ki Pūrehuroa (Massey University) in Te Whanganui-a-Tara (Wellington) on Te Āti Awa (traditional Māori lands) of Aotearoa (New Zealand) in fulfillment of the requirements for the degree of Master of Creative Enterprise (MCE) within Te Rewa o Puanga (the School of Music and Creative Media Production) - Moneymaker, Kelly (Massey University, 2022)
This thesis explores cultural meaning-making in documentary filmmaking as a process that places storytelling in local hands by positioning the filmmaker as a listener-facilitator to find a space for mutual knowing between Western and Indigenous worldviews. The critical analysis applies an Indigenous, comparative decolonial lens to Multiple-eyed Seeing as it relates to creative arts practice and Indigenous methodologies that empower local Native voices to challenge popular conventions in documentary production. Creative arts pedagogies are studied while working with a transcultural framework, drawing upon Indigenous guiding principles of Inupiat, Māori, and Samoan peoples. Research methods include community-based participatory action research (CB-PAR), autoethnography, narrative reflection; and co-creative processes of collaborating with Elders, localhost, and crew members. This all grounds the ethical pursuit of cultural restoration, empowerment, self-determination, reciprocity, and agentic representation. This work is meant to support others wishing to co-create media with Indigenous communities. I submit this thesis to reclaim Indigenous voices through the process of documentary filmmaking.
Keywords: Indigenous; indigenous knowledges; knowledge-holders; two-eyed seeing; multiple-eyed seeing; decolonization; Native; localhost; autoethnography; 360599 Screen and digital media not elsewhere classified; 451999 Other Indigenous data, methodologies and global Indigenous studies not elsewhere classified